Movimentos migratórios e a questão habitacional na produção do espaço urbano em Serra (ES) no período entre 1960 e 2000 - Suce, Dourine Pereira Aroeira (2018)
It is the main question of this work to investigate to what extent the migratory phenomena present between the decades of 1960 and 2000 contributed to the production of the space and the aggravation of the social inequalities manifested in the lack of housing in Serra. The objective is to identify the relationship between migratory flows and the production of space and the social reproduction of capitalist relations in the aggravation of social inequality. It contextualizes the discussion of the production of space in the contemporary capitalist city, the urban and migratory phenomena and the interconnections with the manifestation of the social question, categories constructed and produced socially composing the tessitura of urban space. The lack of housing constitutes a transversal axis of analysis, conceived as one of the expressions of the social question inherent in the development of capitalism, cooled by urban and migratory phenomena. It refers to the socio-historical analytical study, based on qualitative and quantitative approaches based on a bibliographical and documentary study in a grouping of demographic, primary and secondary sources, on the subject.